Analisis Kejadian Pernikahan Dini di Desa Kawat Kecamatan Tayan Hilir Kabupaten Sanggau Propinsi Kalimamtan Barat - Fajar Yousriatin (Raheema, 2018)
Early marriage is a marriage that has happened to a person with the status of women under 20 years of age. Figures early marriage almost found throughout the Province of Indonesia, approximately 10% of young women had their first child at the age of 15-19 years. The research aims to understand and explain the factors related to Genesis Early Marriage In the Kawat village of Tayan Hilir Sub district Sanggau Regency West Kalimanan Province in 2016.Research design used in this study was cross sectional. With a sample of 268 respondents, the sampling technique is done probolity sampling, is simple random sampling.Variables that relate segnifikan namely education level, economic status, pregnancy unwed of marriage, pornography exposure, traditions, knowledge about reproductive health, exposure to information about the risks of early marriage and promiscuity. While most dominant variable is pregnant unwed of marriage. To overcome these local governments to cooperate with BKKBN to more aggressively implement programs to youth genre through training programs in order to get married at an ideal age. To realize these efforts, there must be cooperation of the parents because of the involvement of parents is the most important.